Fabrication of electrospun polylactic acid/polyhydroxybutyrate/silk fibroin nanofibers to obtain retinal nerve fiber layer - ULAĞ, SONGÜL (My University, 2023)
Retinal tissue consists of neural networks in the inner layer of the eye and is the region where the optic nerves connect to the brain. It affects directly visual ability. There are nerve fibers that caring blood tissues in their structure and support vision. These structures may be damaged by external factors or genetic reasons. The properly supported and repaired structures can be obtained by tissue engineering methods. In this study, polylactic acid/polyhydroxybutyrate/silk fibroin nanofibers were fabricated with the electrospinning method. PHB and Silk Fibroin were used to provide biocompatibility to the fiber structure. SEM was used for observing the morphological properties of the nanofibers. The biocompatibility properties of the Polylactic acid/Polyhydroxybutyrate/Silk Fibroin nanofibers were tested with mesenchymal stem cells (MSCs). Additionally, the mechanical properties of the fibers also were analyzed to determine the mechanical strength of the fibers. The degradation and swelling behaviors of the scaffolds were also examined in vitro conditions.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Electrospinning; nanofibers; poly(lactic acid; polyhydroxybutyrate; retinal nerve fiber; silk fibroin.